Analysis of Coastline Changes in West Leihitu District Using Landsat Imagery - Hafiz Syaifudin Pattilouw; Warniyati Warniyati; Tri O Sihombing; Monica R Tutkey (Borneo Engineering: Jurnal Teknik Sipil, 2026)
Coastal areas are currently facing serious threats due to changes in the coastline caused by natural factors such as waves, tides, and ocean currents, as well as human activities such as reclamation, coastal development, and mangrove deforestation. Changes in the coastline can have a direct impact on coastal ecosystems and the lives of surrounding communities, especially in areas where economic activity depends on coastal resources. One area experiencing such dynamics is the West Leihitu District in Central Maluku Regency. This study aims to analyze coastline changes in the West Leihitu District during the period 2015 to 2024 using Landsat 9 satellite imagery and the Geographic Information System (GIS)-based Digital Shoreline Analysis System (DSAS) method. The analysis was conducted spatially and temporally to determine the extent of shoreline shifts, both forward and backward. The image data were processed through radiometric and geometric correction, land-sea boundary delineation, shoreline digitization, and inter-year overlay. The Net Shoreline Movement (NSM) and End Point Rate (EPR) methods were used to calculate the distance and rate of shoreline change. The results of the study show that there were varying changes in the coastline in five coastal villages, namely Larike, Wakasihu, Allang, Liliboy, and Hatu. Larike Village experienced the greatest coastline advance with an average change of 7.05 meters and a rate of 0.78 meters/year, followed by Wakasihu Village with an average of 6.69 meters and a rate of 0.74 meters/year. Meanwhile, Allang and Liliboy villages showed a tendency for shoreline retreat, with average changes of 4.25 meters and 0.85 meters, respectively. Hatu village experienced relatively small changes and tended to be stable.